A narrativa distópica juvenil : um estudo sobre Jogos Vorazes e Divergente - Rodrigues, Paula Martins (2015)
The twentieth century was affluent in dystopian narratives, which arose from a specific historical moment, expressing the anxieties and fears that people had in that moment. It is possible to perceive common influences among such works, as the dictatorships that ravaged Europe during the World Wars and the ambiguous role of progress and science within this context. With the beginning of the new millennium, there was a significant return of these narratives, this time to the young audience, leading us to question ourselves about the reason that made them become relevant to these young readers and about the possible traits of our time that lead them to fear the present and the future. Thus, this master’s thesis aimed to understand the way the young adult dystopias functioned and to perceive how they differed from those written in the twentieth century, attempting to delineate a possible profile and also to encourage more discussions about these literary works. For this purpose, we explored the universe of the trilogies The Hunger Games and Divergent, written by the Americans Suzanne Collins and Veronica Roth, and we used the theoretical works of authors that engaged themselves to examine the dystopias and utopias, as Chad Walsh, Jerzy Szazhi and Keith Booker, and also other social theorists, as Michel Foucault and Slavoj Zizek. We discussed about Young Adult literature, the rising of dystopias in the twentieth century and the manner how these works set their societies.